Social and Environmental Disclosure in Corporate Annual Reports: Evidence from Kuwait - Hewaidy, Aly M (International Journal of Social Sciences and Management, 2016)
With the lack of empirical research in voluntary disclosure in the Middle East area, the present study aims at investigating and evaluating corporate social and environmental disclosure (CSED) practices in Kuwait. To achieve this objective, a checklist of 25 social and environmental disclosure items was developed. These items were then classified into four categories: human resources, environmental activities, community involvement and product/service related information. Using content analysis, the 25 disclosure items were applied to the annual reports of a sample of 43 companies listed in Kuwait Stock Exchange (KSE). It was found that the overall disclosure level for the sample companies is 21%. The disclosure level varies by disclosure category. Product/service related information achieved the highest disclosure level (43%), while human resources disclosure comes second (25%). Little attention was given to disclosing information related to community and environment, with a disclosure level of 16% and 8% respectively. These results suggested that there is a significant scope for additional social and environmental disclosure in the annual reports of Kuwaiti companies. Issuing regulations and guidelines on CSED is needed to motivate Kuwaiti companies to improve their social and environmental disclosures. Int. J. Soc. Sci. Manage. Vol-3, issue-1: 8-16